(3aQGFO GdCWhGb aj CLjGO eMGSf GdCNdGb ef CfHGA EHQGgje Hf Ydi GdCMOH GdWQGHdSi GdMfajs - (3GdGMOH , EHQGgje Hf Ydj GdGMOH GdWQGHdS GdHjQhJj, GdGMOH,J (B1308 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CMeO Gddg GdcQje CeG HYO ajbhd EHQGgje Hf Ydi GdCMOH GdWQGHdSi gPg OQQ efKhQ , hZQQ efXhe ai YbhO GdfMhQ CHQRJgG Ydi efUI GdHdGZI eGFI ebGdI s
(3BNQgG (B:s
(3hGdMeO GdMbjbI dc ai GdEHJOGA hGdEfJgGA hGVQY Edjc Cf dG XeC hdG CVMi ai jhe GdRMGe hCf JaJM Ydi ef ehGgH cQec eG CahR efg HMSf GdNJGe s
(3HgG fXGe GdJYbjHIs
(3cJHJ CQbGe GdebGdGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B61s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs